Translating the Strengthening and Stretching for Rheumatoid Arthritis of the Hand Programme from clinical trial to clinical practice: An effectiveness-implementation study - TONGA, EDA (SAGE PUBLICATIONS LTD, 2020)
Introduction: The Strengthening and Stretching for Rheumatoid Arthritis of the Hand programme is a hand exercise programme for people with rheumatoid arthritis. It was clinically effective when delivered during a clinical trial but there was a need to evaluate translation into routine care. Methods: We conducted an effectiveness-implementation study. We adapted the trial training into an online format for National Health Service hand therapists. Educational outcomes included confidence and capability to deliver the programme. Implementation outcomes included training reach and adoption. Therapists were invited to collect clinical outcomes. Patients receiving the programme provided data on function (Michigan Hand Questionnaire function scale), pain and grip strength at baseline, treatment discharge and four-month follow-up. Results: A total of 790 therapists (188 National Health Service organizations) enrolled in the training; 584/790 (74%) therapists (162 National Health Service organizations) completed the training; 448/790 therapists (145 National Health Service organizations) (57%) evaluated the training and were confident (447/448, 99.8%) and capable (443/448, 99%) to deliver the programme with 85% intending to adopt it (379/448). Follow-up data were provided by 116/448 (26%) therapists. Two-thirds (77/116; 51 National Health Service organizations) reported adopting the programme. One hundred and eighteen patients (15 National Health Service trusts) participated. Patients reported improved function (mean change Michigan Hand Questionnaire scores: 10 (95% CI 6.5-13.6) treatment discharge; 7 (95% CI 3.8-10.2) 4-month follow-up). Grip strength increased 24.5% (left) and 31% (right). Pain was stable. Discussion: Online training was an effective way to train therapists with good reach. Clinical outcomes were similar to the clinical trial providing preliminary evidence of successful translation into routine care.
Keywords: Implementation; hand exercises; rheumatoid arthritis; online training; KNOWLEDGE; SARAH